Mechanism of magnetic transition in FeCrCoNi-based high entropy alloys - Huang, Shuo; Li, Wei; Li, Xiaoqing; Schönecker, Stephan; Bergqvist, Lars; Holmström, Erik; Varga, Lajos Károly; Vitos, Levente (Materials & design, 2016)
First-principles alloy theory and Monte-Carlo simulations are performed to investigate the magnetic properties of FeCrCoNiAlx high entropy alloys. Results show that face-centered-cubic (fcc) and body-centered-cubic (bcc) structures possess significantly different magnetic behaviors uncovering that the alloy's Curie temperature is controlled by the stability of the Al-induced single phase or fcc-bcc dual-phase. We show that the appearance of the bcc phase with increasing Al content brings about the observed transition from the paramagnetic state for FeCrCoNi to the ferromagnetic state for FeCrCoNiAl at room-temperature. Similar mechanism is predicted to give rise to room-temperature ferromagnetism in FeCrCoNiGa high entropy alloy. [Display omitted] •Curie temperature of high entropy alloys predicted from first principles.•Phase-induced magnetic transition mechanism in FeCrCoNiAlx system.•FeCrCoNiGa: an alternative ferromagnetic high entropy alloy at room temperature.